Singapore : 2017 Article IV Consultation-Press Release; Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Singapore's economic growth momentum has improved since late 2016, supported by a recovery in global electronics trade. Real GDP grew by 2.7 percent in the first quarter of 2017 (year-over-year). However, the recovery has not yet been broad based and private domestic demand, particularly private investment, remains subdued. Labor market conditions have softened with two consecutive years of weak net employment generation. Singapore's growth is projected in a 2.5-3 percent range over the medium term, with the growth rates rising as improvements in productivity take hold. In the near term, real GDP will grow by about 2.25 percent in 2017 and 2.5 percent in 2018.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet